Anselm and Abelard: Investigations and Juxtapositions. Edited by G. E. M. Gasper and H. Kohlenberger - Evans, Gillian (The journal of theological studies, 2007)
Anselm and Abelard were contemporaries, though Abelard was of a younger generation and as far as we know they never met. A link between them was the fact that both were attacked by Roscelin of Compiègne, who, in the already competitive world of very early medieval academe, seems to have sought to make his name by undermining the reputations of more ‘established’ figures., Medievalists have tended to circle a little uneasily round the difficulties of comparing the two. Anselm died just short of the period when the schools of northern France were beginning to evolve in the direction which would, within a generation, create the first universities. Abelard took an active part in fostering those developments.